An Analysis of the Impact of Variations in Rasm and Qira’at Diversity on the Meanings of the Qur’an - Dr. Sumayyah Rafique (`, 2025)
The Noble Qur’an is the sacred and infallible Word of Allah, a complete and perfect code of guidance, light, and life for people of every era and generation. This Book of Guidance is not only miraculous in its words, meanings, and teachings, but also in the remarkable and unparalleled system through which it has been preserved. Allah Almighty, in His divine grace, has ensured the preservation of every aspect of the Qur’an—its words, meanings, and even its modes of recitation and pronunciation. Among these essential aspects are two scholarly and technical dimensions, namely, the Rasm Uthmani (Uthmanic script) and the diversity of Qira’at (variant readings), both of which have profoundly influenced the understanding, interpretation, and recitation of the Qur’an.The term Rasm al-Qur’an refers to the style of script that was specifically adopted during the caliphate of the third Caliph, Uthman ibn Affan (may Allah be pleased with him), in the official transcription of the Qur’anic manuscripts. This script is not merely a technical writing method, but a foundational system that encompassed the diversity of the Seven and Ten Qira’at and supported the variant readings of different Qur’anic reciters. This system of transcription not only unified the recitation of the Qur’an but also enriched and deepened its understanding.The diversity of Qira’at refers to those mutawatir (mass-transmitted) recitations of the Qur’an that were transmitted from the Prophet Muhammad (peace be upon him) through various Companions. These recitations exhibit differences in pronunciation, vowelization, grammatical structures (sarf and nahw), and even in the orthographic forms of certain words. These variations are not intended to create contradictions in meaning, but rather to manifest the miraculous nature, eloquence, and semantic richness of the Qur’an. This diversity served as a great facilitation by accommodating the dialectical variations of different Arab tribes and easing the recitation for them. It also played a significant role in ensuring the accuracy and correctness of the Qur’anic text. For this reason, eminent scholars, hadith experts, and exegetes of the Muslim ummah not only accepted this diversity but also regarded it as a means of enhancing the depth and breadth of Qur’anic understanding. Keywords: Impact of Variations, Rasm and Qira’at, Noble Qur’an, Mutawatir Recitations, Qur’anic Interpretation, Dialectical Facilitation